Credit card usage and inflation: a case study of a small open economy - Wong, Zoey Jia Rou; Tang, Tuck Cheong (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examined the influence of credit card usage on inflation in a small open economy, Malaysia. The existing studies used money supply, and bank lending as the key monetary determinants of inflation in Malaysia. These two variables had also been re-examined separately for comparison purpose. Other macroeconomic variables were economic activity and imports. The paper employs The Autoregressive Distributed Lag (ARDL) approach using time series data with monthly observations over 1997-2017. The results of this study showed that the price level, the imports and economic activity were cointegrated. In the long-run, credit card usage was more elastic than bank lending. The economic activity remained the most elastic determinant of price level. In the short-run, bank credit growth, and money supply growth determine the inflation. Meanwhile, imports growth and economic growth did not influence the inflation. The past inflation rates were found to be informative to the current inflation. Hence, this study suggested that inflation in Malaysia was due to ‘too much financing’. This study also provided policy implications